Valdosta Project Change, Scrapbook, October 1999 - Valdosta Project Change (Lowndes County Historical Society, 1999)
10/2- Study shows America’s bound by race: Stereotypes affect labor, housing markets- Associated Press; 10/6- County schools seek community support: Officials’ new program to be sponsored through private sector- Weenam Chua; 10/6- Offense not intended- Matt Flumerfelt, Valdosta; 10/13- Public forum was missing the public: More than half the people who attended were school officials- Weenam Chua; 10/18- Candidates face questions at public forum: Williams’ death a major topic- Emma Johnson; 10/28- Racism isn’t just black against white- Abigail Van Buren; 10/30- State wants race policy upheld- Associated Press; 10/30- Power of Prayer- Elizabeth Butler;
Valdosta Project Change. “Valdosta Project Change Scrapbook, October 1999,” Lowndes County Historical Society. Valdosta State University Archives and Special Collections, MS-181; Valdosta Project Change Scrapbook Collection, 1997-2003. 1 PDF document and scans, 9 pages. 225 MB (236,957,620 bytes).
Keywords: Clippings (Books, newspapers, etc.); Discrimination--Prevention; Lowndes County Historical Society (Valdosta, Ga.); Nonprofit organizations; Project Change; Race discrimination--Prevention; Racism; Scrapbooks; Valdosta (Ga.) -- Social conditions; Valdosta (Ga.); Valdosta Daily Times; Valdosta Project Change